Pengaruh Lingkungan Kerja dan Budaya Organisasi Terhadap Kinerja Tenaga Kependidikan (TNDK) Melalui MotivasiPada Institut Teknologi dan Bisnis Indragiri - TRIYONO, ARIS (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
It is suspected that the performance of the Indragiri Institute of Technology and Business Education Staff is still not optimal. This is influenced by several important factors, including the work environment, organizational culture, and the role of motivation. A less conducive work environment and an unsupportive organizational culture can reduce the enthusiasm and productivity of educational staff.This research was conducted at the Indragiri  Institute of Technology and Business. The aim of this research is to determine the influence of the work environment and organizational culture on the Performance of Education Personnel at the Indragiri Institute of Technology  and Business through their motivation.The method used in this research is a quantitative method, the sample is 59 people, census sampling method or saturated sample; Types and sources of data, types of quantitative data, primary data sources; Data collection techniques, Interviews, Questionnaires; The data analysis method used is a statistical analysis method using IBM SPSS  21 software; Instrument test; Validity test; Reliability test; Classic Assumption Test: Normality test, linearity test; Model feasibility test (F test); Path analysis (Path Analysis); Multiple correlation coefficient (R); Coefficient of determination (R2); Hypothesis test (t test). The research results show that the work environment influences motivation. Organizational culture influences motivation. The work environment influences the performance of educational staff. Organizational culture influences the performance of educational staff. Motivation influences educational staff. The work environment through motivation has no effect on the performance of educational staff. Organizational culture through motivation has no effect on the performance of educational staff.